Effects of running experience on coordination and its variability in runners - Floria, P.; Sánchez-Sixto, A.; Ferber, R.; Harrison, A. J. (Journal of Sports Sciences, 2018)
The purpose of this study was to examine the differences in coordination variability in running gait between trained runners and non-runners using continuous relative phase (CRP) analysis. Lower extremity kinematic data were collected for 22 participants during the stance phase. The participants were assigned to either a runner or non-runner group based on running volume training. Segment coordination and coordination variability were calculated for selected hip-knee and knee-ankle couplings. Independent t-tests and magnitude-based inferences were used to compare the 2 groups. There were limited differences in the CRP and its variability among runners and non-runner groups. The runners group achieved moderately lower coordination compared with non-runners group in the phase angle for hip abduction/adduction and knee flexion/extension. The runners tended to show moderately lower coordination variability in the phase angle for knee flexion/extension and subtalar inversion/eversion in comparison to non-runners group. These results suggested that levels of experience as estimated from weekly training volume had little influence on coordination and its variability.